Neutralization and hemagglutination-inhibition antibodies following influenza vaccination of HIV-infected and HIV-uninfected pregnant women. - Marta C Nunes (PLoS ONE, 2018)
Background We previously reported that despite HIV-infected pregnant women had modest humoral immune responses to inactivated influenza vaccine (IIV) measured by hemagglutination-inhibition (HAI) assay, the observed vaccine efficacy against influenza disease was higher than predicted by HAI; suggesting that IIV may confer protection to HIV-infected individuals by additional mechanisms. We evaluated the response to IIV by microneutralization (MN) and HAI assays and correlated both methods in HIV-infected and HIV-uninfected pregnant women. Methods MN and HAI antibodies were measured pre-vaccination and approximately one-month post-vaccination in 80 HIV-infected and 75 HIV-uninfected women who received IIV. Geometric mean titers (GMTs), fold-change in titers and seroconversion rates were determined for the three influenza stains in the vaccine. Results After vaccination there were significant increases in MN and HAI GMTs for the three vaccine strains in both HIV-infected and HIV-uninfected women. HIV-infected women had, however, a lower immune response compared to HIV-uninfected. Fold-increases were 2 to 3-times higher for MN assay compared to HAI assay for the influenza-A strains. Also a higher percentage of women seroconverted by MN than by HAI assay for the influenza-A strains. There was high positive correlation between MN and HAI assays, except for the B/Victoria strain at pre-vaccination. Conclusions In general, the MN assay was more sensitive than the HAI assay. Microneutralization antibodies might correlate better with protection against influenza infection.